The effect of probiotic therapy on quality of life and depressive symptoms in patients with diarrhea-predominant irritable bowel syndrome (Annals of Medical Research, 2023)
Aim: The aim of this study was to analyze the effect of probiotics on quality of life and depressive symptoms in patients with diarrhea-predominant irritable bowel syndrome (IBS) and moderate or severe depressive mood.Materials and Methods: Patients diagnosed with diarrhea-predominant IBS using the Rome IV criteria and Bristol Stool Form Scale and with moderate or severe depressive symptoms according to the Beck Depression Inventory comprised the study participants. The patients were randomized and divided into two groups as the medication only group and the medication + probiotic group. The IBS 36 questionnaire and Beck's Depression Inventory were administered to all patients in the first and second groups and the scores were recorded.Results: The change in IBS-36 scores from the beginning to the 10th week was significant in both groups (p
Keywords: Irritable bowel syndrome; Diarrhea; Probiotics; Depression